Soil chemical attributes, root growth and rice yield according to slag application - Carvalho-Pupatto, Juliana Garcia; Büll, Leonardo Theodoro; Crusciol, Carlos Alexandre Costa (Pesquisa Agropecuaria Brasileira, 2004)
Use of industrial residues as alternative sources of nutrients to the plants is due to the necessity of reducing their accumulation in the production sites. The objective of this work was to evaluate the effect of metallurgy slag in soil chemical attributes, in development and in grain yield of upland rice sprinkler irrigated. The experiment was carried out in a randomized block design, with three treatments constituted by two scums, blast furnace (196 g kg-1 of Si) and steel slag (56 g kg-1 of Si), and a control without application, with eight replications. The scums can be used as corrective of soil acidity and silicon source. Alterations in the soil chemical attributes are related to the chemical composition of the scums. Blast furnace slag resulted in higher root growth in depth and better distribution in the profile soil provides higher shoot dry matter yield and grain yield.